ANALISIS STRATEGI PEMASARAN KERUPUK MAWAR DI UMKM CITRA DENGAN METODE SWOT DAN QSPM - KHADIJAH, AFNI; Dhamara, Willy; Wijaya, Hartadi (Prodi Teknik Industri, Fakultas Teknik, 2023)
Marketing strategies are needed by Citra MSME actors to face competition in the target market. This research is a type of qualitative and quantitative research with the use of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) methods as data analysis. And it is supported by the use of IFAS (Internal Factor Analysis Strategy) matrix, EFAS (External Factor Analysis Strategy) matrix, SWOT matrix, SWOT diagram, and QSPM matrix as the decision making. The purpose of this study is to determine the appropriate marketing strategy applied to the Citra City of Serang SMEs according to the internal and external environment owned. The results of this study indicate that the results of the IFAS matrix are 3,246 and the results of the EFAS matrix are 3,213. So that on the SWOT diagram it can occupy a quadrant 1 position, which means that MSMEs The environmental image of Peksrungan is in a strong position and has many opportunities. In accordance with the results of the SWOT matrix and the QSPM matrix, the appropriate strategy to be applied is the W – O Strategy with a rank 1 in the QSPM matrix 1. Increasing promotions to offset the promotion of new competitors and utilizing social media to show product quality 2. Marketing is expanded to the Ciruas - Cikande area as a measure to expand the distribution area.